EFFECT OF ENERGY RADIANT LASER ON PHOTOANTIMICROBIAL TO DEGRADATION STAPHYLOCOCCUS EPIDERMIDIS BIOFILM CELLS MEDIATED SENSITIZER OF NANO SILVER-CHLOROPHYLL JATROPHA LEAF - Astuty, Sri Dewi; Handayani, Yusri; Abdullah, Rismayani; Hajar, St.; Tabaika, Pryandi M. (Indonesian Physical Review, 2023)
Chlorophyll compounds have been widely developed in photoinactivation research as organic photosensitizer agents, especially those extracted from green plants. Besides being natural and containing antimicrobial substances, the characteristic electronic properties of chlorophyll atomic have a long lifetime at the triplet level, so it is highly probable to produce Reactive Oxygen Singlet (ROS) while light activates. This phenomenon can potentially be applied in the mechanism of Photodynamic Therapy (PDT) or Photodynamic Inactivation (PDI) in various types of pathogenic bacteria that trigger infectious diseases. Laser light that activates photosensitizer molecules produces singlet oxygen which is reactive and toxic to microbial pathogens. In this study, will be found the efficacy of Jatropha leaf extracts combinate nano silver to inactivate biofilm cells of Staphylococcus epidermidis after being inducted by a red laser. Analysis of the research data quantitatively and qualitatively described the reduction in the number of biofilm cells and damage to the morphology of the biofilm cells with various energy radiant lasers applied through a scanning electron microscope (SEM) profile. The results showed that the photosensitizer agent, which combined Jatropha extracts with nano silver, obtained an inhibitory effect of 60% for the non-oxygenated group and 80% for the oxygenated group.